Membangun Kepribadian yang Berkarakter sebagai Upaya Membentuk Remaja Berkualitas - Herio Rizki Dewinda; Ummil Khairiyah; Yusvi Diana (Majalah Ilmiah UPI YPTK, 2021)
The problems faced by teenagers in recent times have focused more on various delinquency committed by teenagers ranging from drug problems, brawls, bullying cases and other problems. The increasing number of problems faced by adolescents indicates the lack of attention from parents and society to the development of adolescent character. Facing this problem, one solution that can be used is to strengthen the character of youth through character education. Character education is considered the best choice in preparing future generations because it can be both preventive and curative. In this community service program, the training method is used to convey the basics of character education. This Character Personality Training Program aims to invite teenagers to recognize their potential and be able to interact well with their social environment. This training program was given to 30 teenagers who are members of the Padang Japang Mosque Youth Association (IRMPJ). The results of the training show that there is an understanding of adolescents about the importance of understanding themselves and having good character in socializing. Besides that, a continuous program is also needed so that the stages of the material provided can be carried out perfectly.